2019
DOI: 10.3390/brainsci9060124
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Changes in Injured Rat Spinal Cord Following Electrical Brainstem Stimulation

Abstract: Spinal cord injury (SCI) is a major cause of disability and pain, but little progress has been made in its clinical management. Low-frequency electrical stimulation (LFS) of various anti-nociceptive targets improves outcomes after SCI, including motor recovery and mechanical allodynia. However, the mechanisms of these beneficial effects are incompletely delineated and probably multiple. Our aim was to explore near-term effects of LFS in the hindbrain’s nucleus raphe magnus (NRM) on cellular proliferation in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
(94 reference statements)
0
2
0
Order By: Relevance
“…To better understand the proximate causes of improved recovery with NRM stimulation, this and some other studies have focused on more acute, post-injury endpoints and shorter stimulation periods. An immunostaining study of 3-day C5 injury after 2 days of NRM stimulation showed changes in numbers of inflammatory cell types and a transition from neural precursors to radial glia that facilitate differentiation (Jermakowicz et al, 2019). In rats with 3-day T8 contusions, 2 h of NRM stimulation, as in the present protocol, restored normal levels of injury-depleted cAMP, phosphorylated cAMP response binding element (pCREB), and pPKA (Carballosa-Gonzalez et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…To better understand the proximate causes of improved recovery with NRM stimulation, this and some other studies have focused on more acute, post-injury endpoints and shorter stimulation periods. An immunostaining study of 3-day C5 injury after 2 days of NRM stimulation showed changes in numbers of inflammatory cell types and a transition from neural precursors to radial glia that facilitate differentiation (Jermakowicz et al, 2019). In rats with 3-day T8 contusions, 2 h of NRM stimulation, as in the present protocol, restored normal levels of injury-depleted cAMP, phosphorylated cAMP response binding element (pCREB), and pPKA (Carballosa-Gonzalez et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Spinal cord injury is an important cause of disability due to paralysis and loss of function as well as frequently associated neuropathic pain. Jermakowicz et al evaluated the mechanisms underlying low-frequency electrical stimulation and the ability of stimulation to improve motor recovery and lessen allodynia related to spinal cord injury [5]. In the experiments performed, rats received a spinal cord injury at the cervical spinal level.…”
mentioning
confidence: 99%